The Political Economy of Too-Big-To-Fail - J. Atsu Amegashie (Center for Economic Studies and ifo Institute (CESifo), 2018)
I consider a two-period model in which being “too big” is only a necessary condition for an insolvent firm to receive a government bailout because, in addition to meeting a threshold asset size, the firm must engage in a lobbying contest in order to be bailed out. The firm has a political advantage because its probability of winning the contest is increasing in its size. When the firm experiences an unfavorable price shock, I find that the balance between the size of the requisite bailout and the firm's political advantage of being "too big to fail" determines the firm's probability of getting a bailout. Surprisingly but consistent with the US government's differential treatment of Lehman Brothers and Bear Stearns during the 2008-2010 financial crisis, I find that a smaller firm may receive a bailout while a bigger firm will not, although both firms meet the threshold size of “too big to fail” and a firm's political advantage is increasing in its size.
Keywords: O10; P16; P48; 330; insolvency; bail-out; biased contest; political advantage; too-big-to-fail